A Compact Antenna With Multiple Stubs for ISM, 5G Sub-6-GHz, and WLAN - Azimov Uktam Fakhriddinovich; Md. Abu Sufian; Wahaj Abbas Awan; Niamat Hussain; Nam Kim (IEEE Access)
This article describes the design of a tri-band antenna that operates at 2.45 GHz (ISM band), 3.5 GHz (5G sub-6-GHz band), and 5.8 GHz (WLAN band). The antenna design is inspired by a conventional quarter-wave monopole which is fed using a coplanar waveguide feed. Initially, the radiator is loaded with an inverted L-shaped stub to attain broadband across the band spectrum of 2.4 GHz. Then, a pair of two open-ended stubs are etched to achieve a higher frequency band of 5.8 GHz. Hereafter, another open-ended stub is loaded to the right end of the radiating structure, which results in the generation of the Sub-6 GHz 5G (3.5 GHz) band. Finally, the antenna is optimized using parametric analysis to improve the impedance matching across all bands. The proposed antenna offers a tri-band operational mode having frequency ranges from 2.38–2.51 GHz, 3.44–3.84 GHz, and 5.53–7.23 GHz. The reported gains of the proposed antenna at respective frequencies are 2 dBi, 2.1 dBi, and 2.5 dBi having an omnidirectional stable radiation pattern. The antenna prototype is created on a small $20× 16×1.6$ mm3 board and measured to validate the results. Furthermore, the performance of the antenna is compared with the state-of-the-art works to demonstrate its key advantages over similar designs.